A comparative study of women entrepreneurship in transitional economies: The case of China and Vietnam. Issue 1 (19th October 2018) - Zhu, Lei; Kara, Orhan; Zhu, Xiaowei
Abstract : Purpose: The purpose of this paper is to compare women entrepreneurship in China and Vietnam by examining the motivations, success factors and problems related to establishing women-owned businesses. Design/methodology/approach: The sample in this study consisted of 170 women entrepreneurs in Vietnam and 180 women entrepreneurs in China. The authors used the survey instrument developed by H.M. Chu (Chu and Katsioloudes 2001 ), which has been adopted in a number of small business studies since 2002. To determine whether there is a significant difference between the two countries regarding each factor of motivations, success factors and problems, the authors use the non-parametric Wilcoxon rank-sum test. Findings: Women entrepreneurs are motived to earn more income in both China and Vietnam. Vietnamese businesswomen value intrinsic rewards such as gaining personal satisfaction and freedom. They also take business ownership as a way to reduce work–family conflict. Demonstrating the ability and gaining public recognition play a more important role when Chinese women entrepreneurs decide to establish their businesses. Both Chinese and Vietnamese women agree that good management skills are essential to achieve their goals. Women entrepreneurs in both countries share similar challenges, such as the inability to recruit and retain employees, severe competition, a weak economy and limited access to financial capital. Practical implications: Given the nature of transitional economies in both countries, the government is required to improve the regulatory environment for protecting private sector employment and private property rights. Policies such as subsidies and tax incentives may assist the development of women enterprises. To support the sustainable growth of women businesses, it is suggested that the government should design effective programs that direct women entrepreneurs to move into high-growth or high-technology sectors. Training programs are also required to improve the knowledge and skills of women entrepreneurs. Making capital accessible to women is also important to stimulate entrepreneurial growth. As a further stimulus, governments should coordinate with financial institutions to provide low-cost loans or even venture capital to facilitate this process. Originality/value: This study is among one of the first attempts to compare women entrepreneurship in the two transitional economies of Vietnam and China. It provides insight into motivations, success factors and problems that women entrepreneurs experienced by examining small business owners in Vietnam and China.